Pemahaman Masyarakat tentang Wakalah dalam Akad Pernikahan Menurut Kompilasi Hukum Islam di Kabupaten Bone - Ilham; St. Habibah (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2018)
The aims of this study are to identify the guardian's motivation in representing the trusteeship to other parties, to identify the practice of wakalah of guardian (wali) in the marriage contract in Bone Regency and to identify the views of community leaders about wakalah of guardian in the marriage contract. The results of the study showed that the community understanding in Bone District In conducting wakalah of guardian on marriage contract is that the community are positive and proud if their sons/ daughters get married under the guidance of religious scholar or teacher. It has become a common tradition among the Bone people to grant the right of guardian in marriage, although the family is possible to do it. Many people think that they are unable to take their children into marriage so they grant their rights as guardian in marriage to local religious leaders or leaders.